Gondang Batak Toba: Makna Religi dan Implikasinya pada Keagamaan dan Adat - Edison R. L. Tinambunan (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Gondang Batak Toba is one of the popular traditions of the Bataks that bestows high artistic and cultural values for music because it has religious meaning important for religious and customary life. This paper aims to find out the religious meaning of gondang implemented in religious and traditional life. This research used a qualitative approach with phenomenological methods. Field data was ob- obtained through interviews with key informants of Gondang Batak Toba from an important traditional city on Samosir Island. The results have shown that the GondangBatak Toba is a religious ritual that can be implemented on religion to support worship and on custom in social life to establish and strengthen civilization. This social meaning is obtained from the religious value of gondang that is expressed in wisdom. These findings contribute to the advancement of social and religious life on Samosir Island.